Effects of α-tocopherol and its derivatives on the NAD(P)H:quinone oxidoreductase 1 level in rat thymocytes - Petrova, G.V.; Donchenko, G.V.; Klimenko К.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
The cytotoxic effects of α-tocopherol short-chain derivatives and α-tocopherylsuccinate on rat thymocytes are accompanied by the proteolytic degradation of DT-diaphorase. The cytoprotective effect of native α-tocopherol is not associated with an increased level of the enzyme.